Excavation of Salt-tolerant QTL in Rice at Bud Stage with High-Density Genetic Map - Lei LEI; Shichen SUN; Liangzi CAO; Guohua DING; Jinsong ZHOU; Liangming BAI; Yu LUO; Tianshu XIA (Guangdong nongye kexue)
【Objective】Excavation of new salt resistance sites in rice bud stage can provide theoretical basis for further gene function analysis and live production of saline soil.【Method】The QTL localization analysis of 169 RIL populations derived from 'Longdao133' and 'Caidao' was conducted by using a high-density genetic linkage map containing 1 107 highquality polymorphism Bin markers. Nine traits, including the coleoptile length, radicle number and radicle length under control condition, the coleoptile length, radicle number and radicle length under 0.5% NaCl treatment, and the relative coleoptile length, the relative radicle number and the relative radicle length, were analyzed for QTL localization analysis.【Result】The high-density genetic linkage map covered 2 957.35 cM of the rice genome, and the average distance between markers was 2.67 cM. The twelve chromosomes contained an average number of markers of 92.25. Descriptive statistical analysis showed that the salt tolerance of parental 'Longdao133' was significantly higher than that of 'Caidao', and the trait phenotypic values of the parents were between the extreme values of the RIL population, and the population showed superaffinity separation. Salt stress severely inhibited the coleoptile length, radicle number and radicle length of the RIL population, and different lines were greatly affected by stress; all traits basically conformed to the normal distribution and had the genetic characteristics of quantitative traits. Linkage analysis identified 19 QTLs that ranged from 2.58% to 14.83%, and identified cloned salt tolerance genes in two QTLs intervals, including DST in the qRTCL3 interval and OsMSRA4.1 in the qRRN10 interval. Moreover, it was found that, the qTCL10 controlling the coleoptile length, qRCL10 controlling the relative radicle length and qRRL10 controlling the relative radicle length under salt stress were located within the same QTL interval. Furthermore, qTRL7, which controlled the coleoptile length, and qRRL7, which controlled relative radicle length under salt stress, were located within the same QTL interval. Analysis results of qRT-PCR of 25 candidate genes within the 2 colocalization intervals showed that LOC_Os07g44210, LOC_Os07g44240, LOC_Os07g44250, LOC_Os07g44350, LOC_Os10g42940 and LOC_Os10g43060 were significantly upregulated in 'Caidao' or 'Longdao133' after salt treatment. Among them, LOC_Os07g44350 was significantly up-regulated in both the coleoptile and radicle of 'Longdao133' after salt treatment.【Conclusion】A total of 19 QTLs associated with salt tolerance at the bud stage of rice were excavated, including two colocalization sites, qTRL7 and qTCL10, and 25 candidate genes in the two colocalization intervals. Six genes were found to be up-regulated after salt treatment by qRT-PCR analysis, and LOC_Os07g44350 was an important candidate for salt tolerance at the bud stage.